An experimental study of resistance of a mixture type semi-planing craft. (15th September 2022) - Shao, Wenbo; Ma, Shan; Zhang, Yifan; Xing, Xiaopeng
Abstract: In this study, a mixture type semi-planing craft is designed in order to improve transportation efficiency of small ship. The natural ventilation technology is used in this craft. When the craft navigates at high speed, air will flow to the ship bottom through the double demi-hull, resulting in resistance reduction. The main purpose of this research is to obtain the resistance characteristic of the semi-planing craft. Towing tank tests were performed for the ship model to obtain the influence of longitudinal center of gravity (LCG) on the ship resistance and attitude, meantime the flow separation phenomenon was observed at bow and stern. The Volumetric Froude number (Fr∇ ) range is from 0.708 to 2.48. Finally, computational fluid dynamics (CFD) method was used to calculate the resistance of semi-planing craft. The resistance results of CFD method were compared with experimental results. In addition, the mixing layer of water and air in hull bottom was observed. In higher forward speed, the distribution of mixing layer becomes more uniform and continuous, decreasing the frictional resistance of semi-planing craft further. Highlights: CFD method was used to calculate the resistance of semi-planing craft and study the flow characteristics.